THE DETERMINANTS OF NON-PERFORMING FINANCING IN SHARIA COMMERCIAL BANKS IN INDONESIA - Indrajaya, Indrajaya (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2019)
The accumulation of non performing financing in economic activities financed by banks can cause problems with the continuity of the bank's operations, if that exceeds certain limits will have potential to stop the bank's activities. This study aims to analyze the influence of bank's internal variables like  FDR, CAR, BOPO and bank external variables like macroeconomic indicators consisting of exchange rates, inflation and GDP (GDP) against non-Performing Financing (NPF) of Islamic Commercial Banks in Indonesia. The data used are monthly industrial time series of Sharia Commercial Banks (BUS) for the period June 2014 to December 2018 sourced from the Islamic Banking Statistics of the Financial Services Authority, the Central Bureau of Statistics (Badan Pusat Statistik) and Bank Indonesia and analyzed using multiple regression methods. The research implications explain the relationship between the internal variables of the bank company (FDR, CAR and BOPO) and macroeconomic variables (Inflation, Exchange and GDP) on the NPF of Islamic banks in Indonesia so that they can be used as input for the relevant authorities in making policies to suppress NPF at a low level. The variables used can provide an overview of the role of the implementation of sharia public bank governance and existing macroeconomic conditions so that it can produce policies and provisions in the field of sharia banking that are effective and on target. The results showed that the CAR variable had a significant effect on NPF with negative influence. Whereas FDR, BOPO, exchange rate, inflation and GDP have no influence on NPF BUS in IndonesiaKeywords: Non Performing Financing, Non Performing Loan, Islamic Commercial Bank, Indonesia.